Educational management: an exploratory study of management roles and possibilities of management development at college level in AJK, Pakistan - Shah, Saeeda (1998)
This study explores college management in the context of a Muslim, post-colonial, LDC (low developing country) situation. The thesis focuses on institutional heads, both male and female, to investigate their roles, practices and the possibilities of management development. It examines the interplay of the discourses of religion, education, management, leadership, and gender, as expressed through the participants’ experiences. Moreover, professional, socio-economic, political, and ideological forces are critically examined as contributive to shaping the discourses and subjectivities, and being shaped in the process.